RELIGION AND POLITICS IN BALI: BALANCING TRADITION AND POWER - Pinatih, I Gusti Ayu Agung Dewi Sucitawathi (JWP (Jurnal Wacana Politik), 2025)
Ritual ceremonies are the core and main thing in the life of Balinese Hindu society. Ceremonies have become part of everyday life that cannot be separated from Balinese life, and ceremonial rituals become the main needs that must be fulfilled as Balinese Hindus. Ritual ceremonies greatly influence the power system that exists in Bali. The growing political trend is that religion has become a key instrument in gaining political support. The purpose of this research is to look at the relationship between religion and the state in the context of local politics in Bali. This research is a qualitative research with literature review technique that examines various relevant literatures. The data used is secondary data derived from journals, websites, newspapers, and archival reports related to the object of research. The data validity technique uses data triangulation which aims to compare different data sources, so that the data produced is valid. The results show that the relationship between religion and the state lies in the attractiveness that religion offers in the electoral process. Balinese Hinduism provides room for politicians to exercise influence. Religious politics that is able to accommodate the ideological and economic needs of society through ritual ceremonies is seen as being able to become a powerful weapon to achieve political support.